Learning and embodying caste, class and gender patternsof childhood in rural Tamil Nadu ; ritual, kinship, gender, and education among Vagri, Mutturājā and Kaḷḷar - Alex, Gabriele (National Folklore Support Center, 2009)
Study conducted in Thanjāvūr District of Tamil Nadu, India.